Gastrointestinal toxicities associated with immune checkpoint inhibitors: a disproportionality analysis leveraging VigiBase, the WHO Adverse Drug Reaction Database - Huang, Sifu; Bai, Xuefeng; Fang, Taiyong; Guo, Yanta; Zheng, Kainan; Lin, Xiahong (Journal of Zhejiang University. B. Science, 2021)
With the improvement of people's living standards, gastrointestinal adverse reactions caused by various adverse factors have attracted more and more people's attention. A recent study has indicated that coronavirus disease 2019 (COVID-19) could also invade the gastrointestinal tract, leading to gastrointestinal adverse reactions ( Song et al., 2020 ). In recent years, immunotherapy has provided certain effects for some patients with advanced malignant tumors. A microencapsulation of immunoglobulin Y (IgY) was reported to provide an effective way to preserve IgY and improve its performance in the gastrointestinal tract ( Zhang J et al., 2020 ). Immune checkpoint inhibitors (ICIs) can significantly improve the survival of some advanced malignant tumors, especially metastatic malignant melanoma and lung cancer ( Afzal et al., 2018 ; Madden and Kasler, 2019 ). They include anti-cytotoxic T lymphocyte-associated antigen-4 (anti-CTLA-4) antibodies (ipilimumab and tremelimumab), anti-programmed cell death protein 1 (anti-PD-1) antibodies (nivolumab and pembrolizumab), and anti-programmed death-ligand 1 (anti-PD-L1) antibodies (atezolizumab, avelumab, and durvalumab) ( Baxi et al., 2018 ). Previous studies have shown that ICI combination therapy, such as nivolumab plus ipilimumab, has particular efficacy in lung cancer, renal cell carcinoma, and malignant melanoma ( Wolchok et al., 2017 ; Derosa et al., 2018 ; Doroshow et al., 2019 ). However, ICIs may also lead to many immune-related adverse events (irAEs), even causing severe complications in certain cases. The most well-established toxicities from ICI therapy are gastrointestinal irAEs, including enteritis, enterocolitis, microscopic colitis, and gastritis, which have attracted public attention in recent years; reports of such events associated with ICI therapy also have increased ( Tandon et al., 2018 ; de Malet et al., 2019 ). These gastrointestinal irAEs may generally respond well to corticosteroids and infliximab ( Haanen et al., 2017 ). Although most of these irAEs are low-grade, a lack of detection and timely treatment may incur severe or fatal complications.